Comparison of the amino acid composition and biological value of protein in fallow deer meat from two farming systems - Anna Kasprzyk (NFS Journal)
The primary aim was to determine the protein content, amino acid profile and the biological value of protein in the longissimus lumborum and the semimembranosus muscles of fallow deer originating from an organic system and a conventional system. This is the first study to analyse the amino acid profile and nutritional value of proteins in fallow deer meat from organic farming system. The muscles were collected from 24 fallow deer carcasses with equal proportions of sex and age. The results demonstrated that the follow deer from the organic feeding grounds exhibited higher exogenous and endogenous amino acid contents and nutritional value. A significant effect of the muscle type on the histidine content and the feeding ground × muscle interaction for glycine was noted. In the proteins from fallow deer muscle tissue the content of exogenous amino acids was higher than in the FAO/WHO protein standard. As data regarding fallow deer meat is limited, the results of this study constitute a valuable contribution to knowledge of the meat protein quality. The data presented in this study can be used by dieticians and by breeders. In light of the high quality and nutritional value of this raw material analysed in this paper, it would be advisable to increase its use in the human diet. This meat can be of particular importance in the diets of children and adolescents as well as the elderly and athletes whose protein requirements are elevated.